Crime and social norms - Garoupa, Nuno (2018)
In this paper, we develop a general equilibrium model of crime. It is shown that law and norms are substitutes in achieving a stable equilibrium. Here we offer a new interpretation of different theories of social norms in the context of crime and deterrence. The law and economics theory is presented as an ‘opportunism- limiting’ approach to norms whereas the evolutionary theory is presented as an ‘opportunity cost’ approach.